Association between role conflict and ambiguity and stress among nurses in primary health care centers in Saudi Arabia during the coronavirus disease 2019 pandemic: A cross-sectional study. Issue 37 (17th September 2021) - Alyahya, Saad A.; Al-Mansour, Khalid A.; Alkohaiz, Mohammed A.; Almalki, Mansour A.
Abstract : Abstract: This study aimed to assess the association between role conflict and ambiguity among nurses in primary healthcare centers (PHCs) in Saudi Arabia and their stress levels during the coronavirus disease 2019 (COVID-19) pandemic. In this online cross-sectional study, sociodemographic and occupational characteristics, role conflict, and ambiguity of 432 nurses were assessed using the Bowling Scale for Role Conflict and Ambiguity and stress was assessed using the 10-item Perceived Stress Scale from September 27 to October 17, 2020. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for above-median stress levels of nurses with average and high (2nd and 3rd tertiles) role conflict and ambiguity compared with nurses with low role conflict and ambiguity (1st tertile). The mean (standard deviation) age of the nurses was 36.5 ± 6.6 years, and 25.9% of them were males. After adjusting for PHC type and working hours, nurses with average and high role conflict had significantly higher stress rates than those with low role conflict, with ORs (95% CIs) of 2.69 (1.62–4.46) and 6.31 (3.78–10.53), respectively. Similarly, nurses with average- and high-role ambiguity had significantly higher stress than those with low role ambiguity, with ORs (95% CIs) of 2.15 (1.30–3.55) and 7.68 (4.54–13.01), respectively. Increasing stress rates were detected across increasing categories of role conflict and ambiguity ( P values for trend <.001). We found that role conflict and ambiguity were associated with stress among nurses in PHCs in Saudi Arabia during the COVID-19 pandemic.